Assyrian Documents in the Musée d'Art et d'Histoire, Geneva - Postgate, J. N.
Middle-Assyrian documents MAH 15854, MAH 16086, MAH 16467, MAH 16130; Neo-Assyrian documents MAH 15929, MAH 16154, MAH 16328.